2001
DOI: 10.1046/j.1365-2044.2001.02059.x
|View full text |Cite
|
Sign up to set email alerts
|

Information and consent for anaesthesia: a postal survey of current practice in Great Britain

Abstract: SummaryA postal questionnaire survey was sent to Royal College of Anaesthetists' tutors in Great Britain and Northern Ireland to gain insight into current practice with regard to information and consent for anaesthesia. Details of consent practice in three specific areas were requested: anaesthesia in general, teaching medical students during anaesthesia and obstetric anaesthesia. Replies were received from 218 tutors (77%). Of these, 72% of departments had a policy on consent for anaesthesia that was in accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…However, according to Watkins et al, only 4.5% of those anesthetic departments used separate anesthetic consent forms. They reported that 70% of departments surveyed documented oral consent on the anesthetic chart, and 72% of departments thought separate anesthetic consent forms were unnecessary [8]. On the contrary, White and Baldwin argued that anesthesiologists should obtain separate, written consent for anesthesia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, according to Watkins et al, only 4.5% of those anesthetic departments used separate anesthetic consent forms. They reported that 70% of departments surveyed documented oral consent on the anesthetic chart, and 72% of departments thought separate anesthetic consent forms were unnecessary [8]. On the contrary, White and Baldwin argued that anesthesiologists should obtain separate, written consent for anesthesia.…”
Section: Discussionmentioning
confidence: 98%
“…Watkins et al reported that 27% of anesthetic departments in the United Kingdom had no departmental policy for consent to anesthesia. They pointed out that inconsistencies might provide grounds for legal challenge [8]. Similarly in Japan, anesthetic departments need to standardize their explanation and promote better communication between anesthesiologists and surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is legally not mandatory before the operative intervention, it becomes a statutory requirement when biomedical research, organ procurement, or medically assisted reproduction is involved [19]. Furthermore, certain centers have begun to seek specific consent for general anesthesia [20] and interventional radiology [21] separate from that obtained by the surgical team. This move has been inspired primarily by medicolegal concerns [22], notwithstanding that the requirement for the former has been specifically rejected by the courts in these islands.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that only 57% of anaesthetic departments surveyed had a written policy for explanation of pain relief options in labour. 13 The OAA leaflet and video 'Pain relief in labour' provide an important source of information for parturients. 14 They also contain some risk information regarding regional anaesthesia.…”
Section: Discussionmentioning
confidence: 99%